3R-BASED LEARNING STRATEGY FOR STRENGTHENING CREATIVITY AND ENVIRONMENTAL CARE ATTITUDE IN ELEMENTARY SCHOOL STUDENTS - Sadek, Azizah Islamiyah St Magfirah Sadek; Erma Suryani Sahabuddin; Muhammad Irfan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Environmental issues, particularly in waste management, remain a significant challenge in elementary schools. The lack of student awareness and low levels of creativity in managing waste call for innovative learning approaches. The aim of this research is to describe the implementation of the 3R method as an effort to enhance creativity and environmental awareness among third-grade students at SD Inpres Pare'-pare', Gowa Regency. The research adopted a Classroom Action Research (CAR) model with qualitative approach. Data acquisition was carried out through various methods, including observation, questionnaires, interviews, and documentation. The study was conducted in two learning cycles, each consisting of planning, implementation, observation, and reflection stages. The results indicate that applying the 3R method has a positive impact on improving students' creativity and fostering their environmental awareness. Students showed greater ability to generate creative ideas using recycled materials and became more engaged in maintaining cleanliness and managing waste responsibly. The learning process became more interactive, with students showing greater enthusiasm in participating in activities to waste management. This improvement was also reflected in the observations where both teachers and students demonstrated active involvement in each stage of the learning process. Therefore, the 3R method can serve as an effective educational strategy to foster environmental values and enhance student creativity from an early age.